Mapping heavy elements in the supernova remnant G290.1-0.8 - Hudaverdi, Murat (Tubitak Scientific & Technological Research Council Turkey, 2018)
We present the imaging and spectroscopic study results of G290.1-0.8 Supernova Remnant (SNR) using the Suzaku X-ray archival data. The SNR belongs to the mixed-morphology class with its centrally peaked asymmetric X-ray core and distorted radio shell-like plasma. The X-ray spectra is well defined with isothermal plasma of kT(e) similar to 0.5 keV. The radial profile shows enhanced elemental abundances. The EW maps reveal inhomogeneous asymmetric spatial distribution of elemental abundances. The northeast of the SNR is bright in Ne, Mg, and Si. The EW maps are enhanced in the direction of the X-ray elongation, suggesting that the distorted X-ray structure is dominated by a core-collapse 20 similar to 25 M-circle dot progenitor star ejecta.
Keywords: Supernova remnants; X-rays; gamma-rays; interstellar medium; X-RAY; EMISSION; EJECTA; SNR-G290.1-0.8; SUZAKU; Physics